BAHAN AJAR E-MOCARI (E-MODUL CANDI ARIMBI) BERBASIS CANVA UNTUK PEMBELAJARAN SEJARAH KERAJAAN HINDU-BUDDHA SEKOLAH MENENGAH ATAS - Artha, Kadek Wisnu (Jurnal Pendidikan Sejarah Indonesia, 2025)
The purpose of this research is to produce teaching materials in the form of the E-Mocari (E-Modul Candi Arimbi) based on Canva. In addition, this research also aims to determine the validity and effectiveness of the product. The research method used in this study is a research and development (R&D) method with a procedural model from Sugiyono, which consists of 10 stages. This product is designed as a learning resource for history that enhances understanding of the importance of studying the history of Hindu-Buddhist kingdoms in Indonesia, particularly regarding Candi Arimbi. E-Mocari contains material on Candi Arimbi, an infographic of the statue of Goddess Parwati, which can be accessed through a QR Code, as well as learning evaluations and answer keys. Students can access E-Mocari through smartphones or laptops both online and offline. E-Mocari can also be shared by downloading the .pdf file format, which makes it easy to access. Based on the results of the data analysis in the expert validation stage, the material expert achieved a percentage of 98.00% with a very valid criterion. The validation results from the instructional materials expert obtained a percentage of 79.00% with a valid criterion. The feasibility test of the product in a small group yielded a result of 83.00% with a very effective criterion. The feasibility test of the product in a large group obtained a percentage of 88.00% with a very effective criterion. Thus, it can be concluded that based on the results of validation by subject matter experts, instructional material experts, and trials with students, the E-Mocari developed in this research is declared very valid and highly effective for use as teaching material in the history lessons of class X-9 at SMA PGRI 1 Jombang.